2022
DOI: 10.1186/s41235-022-00404-7
|View full text |Cite
|
Sign up to set email alerts
|

Habit-like attentional bias is unlike goal-driven attentional bias against spatial updating

Abstract: Statistical knowledge of a target’s location may benefit visual search, and rapidly understanding the changes in regularity would increase the adaptability in visual search situations where fast and accurate performance is required. The current study tested the sources of statistical knowledge—explicitly-given instruction or experience-driven learning—and whether they affect the speed and location spatial attention is guided. Participants performed a visual search task with a statistical regularity to bias one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The critical requirement to establish that habits are inflexible is to make the habitual bias clearly counterproductive for participants (e.g., providing instructions on the change of the spatial distribution of the target or endogenously directing attention elsewhere) and show that the bias remains unchanged. The few studies that have adopted this approach have found that the bias can still be detected but is dramatically reduced, contrary to the inflexibility hypothesis (Golan & Lamy, 2023;Hong & Kim, 2022;Jiang et al, 2014). It is also important that when switching the location of targets or distractors to evaluate if the bias is updated or maintained, we must consider to what extent the new spatial distribution is inconsistent with what participants may have learned during the training stage.…”
Section: Inflexibilitymentioning
confidence: 99%
“…The critical requirement to establish that habits are inflexible is to make the habitual bias clearly counterproductive for participants (e.g., providing instructions on the change of the spatial distribution of the target or endogenously directing attention elsewhere) and show that the bias remains unchanged. The few studies that have adopted this approach have found that the bias can still be detected but is dramatically reduced, contrary to the inflexibility hypothesis (Golan & Lamy, 2023;Hong & Kim, 2022;Jiang et al, 2014). It is also important that when switching the location of targets or distractors to evaluate if the bias is updated or maintained, we must consider to what extent the new spatial distribution is inconsistent with what participants may have learned during the training stage.…”
Section: Inflexibilitymentioning
confidence: 99%
“…Six participants who responded that they had noticed that the target often appeared in a particular location and ranked the rich quadrant as the one in which the shape singleton was most likely to appear were removed. Those participants are expected to have little or no spatial bias, irrespective of target template variation, because attentional guidance by explicit goal is transient 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Yet, there remains the possibility that spatial bias may not be as strong or persistent when the target template is not fixed and unpredictable. Regularity-based spatial bias is known to base distinct attentional mechanism from explicit and goal-driven attention 16 18 , and top-down attention may interact with such bias when required 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Failure to update previously learned regularities can impair behavioral performance, if the old regularities conflict with the new regularity in the altered environment. The flexibility of VSL can be investigated through a two-phase approach (Hong et al, 2022). The initial learning takes place during the first training phase, followed by a subsequent phase where the regularity is changed by introducing new ones.…”
Section: Introductionmentioning
confidence: 99%
“…Flexibility is evaluated by examining how quickly participants adjust their performance to track the updated statistical regularity. In Hong et al (2022), it was found that people could successfully learn the changed spatial regularity which was reflected by the faster RTs for target in the new high-probability region compared to low-probability region which had never served as the high-probability region. Nevertheless, the RTs was still fast for target in the previous high-probability region compared to other low-probability regions and the RTs between trials in which targets appeared at previous and new high-probability region didn't differ, showing that previously learned attention bias persist even when the regularity had changed.…”
Section: Introductionmentioning
confidence: 99%